Aggregation Prone Region analogues: synthetic excipients for protein formulation - Foralosso, Ruggero (2019)
In the last few decades, protein therapeutics have become a relevant segment of the pharmaceutical industry. However, clinical use of biotherapeutics can be limited by poor stability of proteins in the different steps of manufacturing, storage and formulation, with subsequent formation of protein aggregates. Aggregation affects not only therapeutics proteins, with detrimental effects on production costs, final product yields and therapeutic efficacy, but also endogenous proteins, as it leads to the formation of large aggregates deposits which have been correlated to different neurodegenerative diseases. Consequently, a range of stabilisers have been developed to increase the stability of biotherapeutics in formulations, or prevent the aggregation of endogenous proteins. Among the different strategies employed, excipients that stabilise proteins through non-covalent interactions have been reported. This thesis focusses on the stabilisation of proteins through hydrophobic interactions: here, the synthesis of short, hydrophobic, stabilisers is reported. These stabilisers were tested on different proteins, to interact with hydrophobic patches on proteins primary strucures, and block these patches from mutual, self-interactions that may lead to proteins aggregation. In the first part of this work, peptides analogous of hen egg lysozyme Aggregation Prone Region (APR), were synthesised, and tested on lysozyme to verify any potential interaction between these synthetic peptides and their homologous sequence on lysozyme, to block its site from self-interactions that lead to aggregation. For improved solubility and to enhance its stabilising effect, the APR peptide fragment was finally copolymerised with monomer N-hydroxyethylacrylamide, to generate a peptide-polyacrylamide copolymer stabiliser. Pleasingly, the copolymer proved to be able to delay the onset of lysozyme aggregation, which was induced in strong basic conditions. Encouraged by these results, in the second experimental chapter this strategy was expanded by developing a library of amphiphilic block copolymers, comprising hydrophobic amino acid-like moieties, potentially able to non-covalently interact with hydrophobic, self-aggregating protein domains, and prevent protein aggregation/denaturation. Three moieties were chosen, indole 3-acetic acid, phenyl acetic acid and methylisobutiric acid, to mimic the side chains of three amino acids, tryptophan, phenylalanine and isoleucine, respectively. The copolymers were tested on two different proteins, hen egg lysozyme, bovine pancreatic insulin, and the antimicrobial peptide IDR 1018. Potential interaction between the proteins and the copolymers was evaluated under stressful conditions, which induced proteins aggregation, measured by turbidity and solubility studies. Promising stabilising effects were shown by some of the indole-contaning copolymers, which proved to be able to prevent the aggregation and to increase the solubility of both insulin and peptide IDR 1018. Hydrophobic Indole-based oligomers were further tested to evaluate their efficacy in encapsulating the antimicrobial peptide IDR 1018. The peptide was first ion paired with the antimicrobial molecule usnic acid, to develop a hydrophobic complex for enhanced IDR 1018 encapsulation and potential co-delivery of two antimicrobial drugs. In the fourth experimental chapter of this thesis, cholanic-polyacrylamides conjugates were synthesised for potential non-covalent protein conjugation. Cholanic acid has been previously investigated for its ability to interact with proteins hydrophobic patches. In particular, a series of PEG-cholanes of different molecular weight were used to efficiently complex two different proteins, the recombinant human growth hormone (rh-GH) and the recombinant human granulocyte colony stimulating factor (rh‐G‐CSF). improving their bioavailability and extending their half-life. Here, cholanic acid was incorporated into a RAFT agent and used to mediate the polymerization of N-hydroxyethylacrylamide, to develop cholanic-polyacrylamides of different length. The polymers were successfully employed as protein complexing agents for two model proteins, bovine serum albumin and bovine pancreatic insulin. Finally, the last chapter is presented in a form of a draft paper, and is part of a collaborative work started by a former PhD student in our group, Joao Madeira do O. A series of linear and 4-arm glycopolymers, were previously prepared by copper azide alkyne cycloaddition (CuAAC) functionalisation of preformed poly(propargyl methacrylate)s with different sugar azides. In this thesis, the reversible, non-covalent interaction between the small hydrophobic molecule Nile Red and linear and 4-arm glycopolymers was evaluated. Results suggest that the interaction occurs between the dye molecule and single polymer chains, suggesting that these glycopolymers do not self-assemble in supramolecular aggregates and act instead as unimolecular micelles.